Outbreaks of European spruce bark beetle dramatically altered Norway spruce-dominated stands with implications for volant wildlife in the Białowieża Forest, Poland - Andrew Carr; Grzegorz Apoznański; Dorota Dobrowolska; Alek Rachwald (Annals of Forest Science)
Abstract Key message An outbreak of the European spruce bark beetle (Ips typographus L.) in spruce (Picea abies L.) dominated forest stands in the Białowieża Forest, Poland, has led to fundamental changes in forest characteristics. The species composition of regenerating stands now differs from earlier records findings, with oak, birch and rowan becoming dominant, while hornbeam numbers have decreased and Norway spruce is now sporadic, suggesting an ongoing period of reorganisation. Among the forest attributes showing the greatest degree of change are canopy architecture and sheltering opportunities—factors known to be most influential for volant-dependent wildlife. Context The European spruce bark beetle (Ips typographus L.) targets Norway spruce (Picea abies (L.) H.). Once attacked, susceptible trees weaken and die. In planted forests with high proportions of Norway spruce, beetle outbreaks profoundly alter forest structure. The implications of such outbreaks on forest regeneration and their influence on dependent wildlife require ongoing research. Aims We investigated how bark beetle-induced changes in Norway spruce stands alter forest structure characteristics and regeneration, and explored the potential consequences for forest-dependent volant vertebrates. Methods We used a static comparative approach to assess differences in forest structure and regeneration between infested and non-infested Norway spruce stands in the Białowieża Forest, Poland. Eighteen forest variables were measured or derived, including indicators of canopy structure, tree composition, bark features, cavity presence, and microclimate. Sapling composition and regeneration frequency were also recorded to evaluate vegetation dynamics. Data were collected during 2022 and 2023. Results Fifteen forest structural characteristics differed significantly post-infestation, including reduced tree density (trees per hectare), decreased vegetation clutter, and increased light transmittance. Daytime temperatures increased and humidity decreased, while nighttime conditions remained similar. The number of animal shelters in exfoliating bark increased, whereas tree crevices became less frequent. Sapling regeneration was higher in infested stands and dominated by oak (Quercus spp. L.), birch (Betula pendula Roth.), and rowan (Sorbus aucuparia L.). In contrast to earlier research, hornbeam was not the dominant sapling species, and Norway spruce saplings were infrequent. Conclusion While our static comparative approach did not capture temporal dynamics or fully disentangle complex ecological interactions, it provided clear evidence that bark beetle outbreaks dramatically alter Norway spruce-dominated stands. The forest attributes most altered by infestation are well-established drivers of habitat suitability for forest-dwelling volant wildlife. We propose that cyclical beetle outbreaks in spruce-dominated forests act as drivers of accelerated natural succession, shifting species composition from planted Norway spruce to more naturally occurring species. Our findings highlight that bark beetle outbreaks represent natural change, not forest destruction, within this unique European forest ecosystem.